Effects of Jet Induced by String-type Plasma Actuator on Flow Around Three-Dimensional Bluff Body and Drag Force - Takatoshi Matsubara; Yoshiki Shima; Hikaru Aono; Hitoshi Ishikawa; Takehiko Segawa (Energies, 2020)
An experimental investigation of active flow control on a three-dimensional (3D) curved surface bluff body was conducted by using a string-type plasma actuator. The 3D bluff body model tested in this study was composed of a quarter sphere and a half cylinder, and the Reynolds number based on the diameter of half cylinder was set at 1.3 × 104. The modulation drive was adopted for flow control, and the control effects of variations in dimensionless burst frequency (fm+) normalized by the width of the model and freestream velocity were studied. Velocity distributions analyzed by particle image velocimetry showed that the recirculation region behind the model shrank due to the flow control. The static pressure distributions on the back surface of the model tended to decrease under any fm+ set in this study, especially in the ranges of 0.40 ≤ fm+ ≤ 0.64. The drag coefficient reached its maximum value under the similar ranges of fm+. Although the aerodynamic wake sharpening was observed due to the flow control, the entrainment of separated flow into the back surface of the model was enhanced. This scenario of wake manipulation was considered to be responsible for increasing drag acting on the model.